TUGSE-a curious case series unveiled - VG, Mahima; Patil, Karthikeya; Aniyan, Yesoda; Khare, Shikha (International Journal of Dental Research, 2017)
Traumatic ulcerative granulomas are self-limiting ulcero-proliferative lesions emaluating malignancy clinically, thus causing anxiety for the patient. The etiopathogenesis of these lesions are unclear though trauma is ascertained to be a cause. Riga-Fede disease is considered a variant of the same, manifesting in infants. A clinically varying case series of TUGSE and RFD is reported, and the differential diagnosis discussed here.